Deployment guide series. - Moeller, Morten; Bacon, James; Choilawala, Murtuza; Kadijevic, Petar; Rich, Charles R.; Satagopan, Kulasekaran; Vasfi, Gucer (IBM redbooks., 2006)
The IBM Tivoli Change and Configuration Management Database Configuration Discovery and Tracking v1.1 (CDT) is an agentless deep discovery tool that can discover the configuration information of application systems as well as their components and relationships automatically. It also discovers installed hardware and software components in a complex computer server environment and tracks changes to all these components over time. IBM Tivoli CCMDB CDT v1.1 is the core component of the IT Service Management strategy from IBM and fills the role of the Change Management Database for your implementation of ITIL aligned IT processes. This IBM Redbooks publication provides help and recommendations on how to get started deploying Configuration Discovery and Tracking v1.1 and provides step-by-step instructions for setting up and customizing the discovery in your own environment. In addition, it describes the various interfaces that you can use to integrate CDT with your existing IT Service Management processes. The information in this book is intended for IT specialists who design and implement IT Service Management solutions based on IBM Tivoli CCMDB Configuration Discovery and Tracking v1.1.